Perbedaan Perspektif Hakim dalam Putusan Sengketa Pembiayaan Murabahah: Analisis Pertimbangan Hakim dan Keadilan Syariah - Fauziyyah Hasna, Salma (Green Publisher Indonesia, 2025)
The process of forming a judge's decision involves what is known as legal reasoning, which ultimately determines the direction of the judge's perspective in the verdict rendered. Differences in judges' perspectives in murabahah dispute rulings become important to examine further in order to understand why judges can reach different decisions in similar cases. Based on these differing rulings, the study also explores how the principle of justice is applied in judicial decisions. This research employs a normative juridical method using statutory and case comparison approaches. The study concludes that the variation in judges' approaches in considering justice in disputes, both at the first instance and appellate levels, is the reason behind the differing judicial perspectives. This reality indicates that the application of sharia principles in legal practice can vary depending on the judge's focus—whether on substantive or procedural aspects of justice.